2021
DOI: 10.3390/met11121897
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of Compact γ′-γ″ Coprecipitation Strengthened IN718-Variant Superalloy

Abstract: The development of high-temperature heavy-duty turbine disk materials is critical for improving the overall efficiency of combined cycle power plants. An alloy development strategy to this end involves superalloys strengthened by ‘compact’ γ′-γ″ coprecipitates. Compact morphology of coprecipitates consists of a cuboidal γ′ precipitate such that γ″ discs coat its six {001} faces. The present work is an attempt to investigate the microstructure and creep behavior of a fully aged alloy exhibiting compact coprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[6,10,11] Some studies indicated that the δ phase on the grain boundaries may increase the creep resistance via grain boundary serration. [13,14] Desvallées et al investigated the influence of δ phase (amount, shape) on mechanical resistance. [15] They found that the δ phase has a detrimental effect on creep rupture life while no direct effect on LCF life was evident.…”
Section: Doi: 101002/adem202302122mentioning
confidence: 99%
“…[6,10,11] Some studies indicated that the δ phase on the grain boundaries may increase the creep resistance via grain boundary serration. [13,14] Desvallées et al investigated the influence of δ phase (amount, shape) on mechanical resistance. [15] They found that the δ phase has a detrimental effect on creep rupture life while no direct effect on LCF life was evident.…”
Section: Doi: 101002/adem202302122mentioning
confidence: 99%